(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article is about polysemous words and its research, and it provides a definition of polysemous words. The differences between monosemantic words and polysemantic words are also discussed. It has been said that polysemantic words are important for every language, without them, the language will lose its value if we replace each concept with another word. The article gives some ideas about the process of turning monosemantic words into polysemous lexemes, the role of polysemy at the level of the Uzbek language, and the research of polysemous words in Uzbek, Russian and world linguistics.